3PC-060 Hot-melt ram extrusion 3D printing: a smart method for compounding orodispersible films in hospital pharmacies. (March 2019) - Minghetti, P; Musazzi, UM; Selmin, F; Khalid, GM; Franzé, S; Cilurzo, F
Abstract : Background: Orodispersible films (ODF) have been proposed as a valid alternative to conventional oral dosage forms to personalise the therapies and to improve patient adherence, especially in special populations (e.g., dysphagics, paediatrics, geriatrics). Since manufacturing technologies used by the industries (e.g., the solvent-casting technique) cannot be easily applied in a pharmacy setting, alternative methods have been proposed for compounding. 3D-printing permits the preparation of ODF of different strengths and geometries that fulfil the Ph.Eur. specifications concerning the uniformity of dosage units. Purpose: To demonstrate the feasibility of the preparation of ODF by hot-melt ram extrusion 3D printing. 1 Material and methods: This novel technology consists of three simple operations. First, maltodextrins, drug and other excipients (e.g., colourants, flavours, sweeteners) are mixed in a mortar and wetted with the plasticiser (i.e., glycerine). Then, the mixture is fed into the chamber of the ram-extruder and heated. ODF are individually printed using an 18G needle on the packaging material foil and sealed without further manipulation. The critical formulation attributes and process variables were investigated to define the processability space and their impact on the disintegration time and tensile properties of the ODF. The paracetamol (PAR) was used as a model drug to assess the drug-loading capacity of the ODF and the dissolution profile. Results: Preliminary results allowed to the optimization of the process parameters (heating temperature, 85°C; maximum print rate, 50 mm/s; filling angle, 120°) and composition (maltodextrins/glycerine: 80/20 w/w) to obtain homogeneous ODF. The compounded ODF (6 cm 2 ; thickness 150–250 µm) disintegrated in less than 1 min and showed acceptable tensile properties for product handling. Different doses of PAR (12.5, 25, 37.5% w/w) were loaded to such basic composition without altering the ODF performances. The CV% of PAR assay remains lower than 5%. The PAR dissolution profile of printed ODF (t80 <6 min) overlapped that obtained by ODF prepared by the solvent-casting technique. 1 Conclusion: The overall results suggested that hot-melt ram extrusion 3D printing can be used in a pharmacy setting to prepare well-accepted orodispersible dosage forms and to personalise the drug dose according to the needs of the patient. Reference and/or acknowledgements: Musazzi, et al. Int J Pharm 2018;551:52–9. No conflict of interest.